Nutrient dynamics in the berry, bean, and husk of six Coffea canephora genotypes throughout fruit maturation - Henzo Pezzin Salvador; Henrique Duarte Vieira; Ivoney Gontijo; Isabel Marques; José Cochicho Ramalho; Fábio Luiz Partelli (Scientific Reports)
Abstract The coffee plant has high nutritional demands that are lost when the crop is harvested. Understanding the dynamics of nutrient accumulation in the entire plant and on its components during coffee maturation (beans, husk and whole berries) is essential for optimizing mineral supply at different growth stages and for better fertilizer management. To this end, this study evaluated the accumulation of dry matter, macronutrients (N, P, K, Ca, Mg, S), and micronutrients (Cu, Fe, Mn, Zn, B) in the beans, husk, and the whole berries of six Coffea canephora genotypes. Berries were sampled at the end of the grain-filling stage, i.e., 33 weeks after flowering (WAF), and then taken every 14 days over nine periods, concluding at 49 WAF. Our findings reveal that fruit maturation significantly affects nutrient concentration and accumulation in beans, husk, and the whole berries, with the highest concentration typically observed in the fully mature fruits. Nitrogen accumulation was greater in beans, while potassium accumulation was more pronounced in the husk and berries throughout the maturation process. Results allow optimizing fertilization schedules. By using targeted nutrient management practices, coffee growers can avoid over-fertilization, which often leads to environmental issues such as soil degradation and water pollution.